2021
DOI: 10.1101/2021.03.31.21254423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visuomotor brain network activation and functional connectivity among individuals with autism spectrum disorder

Abstract: Sensorimotor abnormalities are common in autism spectrum disorder (ASD) and predictive of functional outcomes, though their neural underpinnings remain poorly understood. Using functional magnetic resonance imaging (fMRI), we examined both brain activation and functional connectivity during visuomotor behavior in 27 individuals with ASD and 30 typically developing (TD) controls (ages 9-35 years). Participants maintained a constant grip force while receiving visual feedback at three different visual gain levels… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 86 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…This can be associated with significant synchronization and temporal coherence dysfunction, decreasing large cortical networks between the two hemispheres from binding temporally and spatially. This can result in a functional disconnection syndrome ( 88 , 102 , 135 , 137 , 279 , 289 , 290 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be associated with significant synchronization and temporal coherence dysfunction, decreasing large cortical networks between the two hemispheres from binding temporally and spatially. This can result in a functional disconnection syndrome ( 88 , 102 , 135 , 137 , 279 , 289 , 290 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 44)]. As these cortical networks become more connected and integrated, they increase the speed of their interaction, and their synchronization improves, allowing more areas to be activated simultaneously (24,39,(278)(279)(280)(281)(282).…”
Section: Discussionmentioning
confidence: 99%
“…He et al used MRI and discovered that the morphological connectivity of the cortical-striatum-thalamus-cortical network of ASD increased and the morphological connectivity of the cortical-cortical network decreased [16]. In addition, several studies have shown that the working memory neural network and visual-motor neural network of ASD exhibit different FC patterns compared to a TD group [67,68].…”
Section: Networkmentioning
confidence: 99%